'I got to understand what it means to be a cancer patient': Qualitative evidence from health professional cancer patients and survivors. (May 2022) - Natuhwera, Germans; Ellis, Peter; Acuda, Stanley Wilson; Namukwaya, Elizabeth
Objective: The study sought to (1) examine healthcare professionals' (HCPs) lived experiences of cancer and (2) generate evidence to inform policy and clinical practice for cancer care. Methods: This was a qualitative study conducted between January and December 2020 on HCPs who were ill with, or who had survived cancer in Uganda. Purposive sampling was used. A demographic form and an open-ended topic guide were used to collect data. Face-to-face and telephone interviews were conducted in English; audio-recorded data was collected until saturation was reached. Colaizzi's framework of thematic analysis was used. Results: Eight HCP cancer patients and survivors from medical, allied health, and nursing backgrounds participated in the study. Their mean age was 56 years (29–85). Five were female. Four broad themes emerged from the interviews: (1) experience of pre-diagnosis and receiving bad news, (2) impact on self and role identity, (3) healthcare system and treatment experiences, and (4) the gaps and what should be done. Conclusion: Cancer patient-hood introduces vulnerability and remarkable disruptions and suffering in nearly all domains of quality-of-life, that is, in professional identity and work, social, emotional, physical, and economic facets of life. Participants identified how they experienced a healthcare system which was costly and staffed by unmotivated staff with limited access to resources, which resulted in many unmet needs and an overall poor experience. Participants identified how, in their view, the healthcare system in Uganda needed to be better resourced, protected by policy and legislation and how cancer awareness among the population needed to be improved.